An overview of factors influencing cancer screening uptake in primary healthcare institutions - Prusaczyk, Artur; Żuk, Paweł; Guzek, Marika; Bogdan, Magdalena; Nitsch-Osuch, Aneta; Oberska, Joanna; Karczmarz, Sabina (Family Medicine & Primary Care Review, 2022)
Screening significantly decreases the severity and incidence of conditions, as well as mortality, and therefore can improve the health of the population. Screening in Poland falls below the acceptable level of 45% of organised screening uptake and the recommended level of 65%. Multidimensional factors have been implicated as barriers and facilitators of screening uptake in the primary care setting. This paper summarises the existing evidence on factors influencing screening uptake in a Pap smear for cervical cancer (CC), mammography screening for breast cancer and faecal occult blood test (FOBT) for colorectal cancer (CRC). We performed a literature search in the MEDLINE (PubMed) and EMBASE databases and included articles of any study design published between 2010 and 2020. We also demonstrate the original concept of ‘Ugly Value’, which describes factors that may reduce screening uptake. Primary care practitioners play a vital role in increasing screening rates in the populations and can improve these rates through a variety of systematically implemented strategies and interventions. We determine four areas to improve cancer screening uptake in primary healthcare institutions: data gathering and data use (IT systems, meaningful use of Electronic Health Records to generate reminders, prompting healthcare professionals to refer patients for screening), cost effectiveness (avoiding overuse of screening in low-risk populations), innovative efficient management (use of effective interventions and thoughtful allocation of resources, e.g. engaging nurses into patient navigation instead of assigning them to answer patient concerns about screening by telephone), organisational system (team based, integrated care and patient navigation are ways to improve screening rates).